Identification of CD161 expression as a novel prognostic biomarker in breast cancer correlated with immune infiltration - Weng, Miaomiao; Xie, Hui; Zheng, Mingjie; Hou, Xinwen; Wang, Shui; Huang, Yue (Frontiers in Genetics, 2022)
Abstract Background: Breast cancer (BC) is the most common cancer which seriously threatens female health worldwide of BC patients. Innovative and effective approaches are urgently needed to improve the prognosis. CD161 has been identified as a promising prognostic biomarker and immune therapy target in other neoplasms, while its potential molecular function has not been fully explained in BC. We aimed at investigating the biological role and clinical value of CD161 in BC. Methods: The CD161 expression was evaluated by TIMER, Oncomine, UALCAN databases and verified by the Gene Expression Omnibus (GEO) database and quantitative real-time polymerase chain reaction (qRT-PCR). The prognostic value of CD161 was assessed via GEPIA, Kaplan–Meier plotter and PrognoScan databases. The Cox regression and nomogram analysis were conducted to further validate the influence of CD161 expression on survival. Gene set enrichment analysis (GSEA), Gene Ontology (GO), and KEGG pathway enrichment analysis were performed to probe the tumor-associated biological process of CD161. CIBERSORT and ssGSEA were employed to investigate the correlation between CD161 and immune cell infiltration, and the result was verified by TIMER and TISIDB. Results: Multiple BC cohorts showed that CD161 was decreased in BC, and high CD161 expression was associated with preferable prognosis. Therefore, we identified the combined model including CD161, age and PR status to predict the survival outcomes (C index=0.78) in BC. Functional enrichment indicated that CD161 and its co-expressed genes were closely related to several cancerous and immunological signal pathways, thus regulating immune response. Moreover, immune infiltration analysis revealed that CD161 expression was correlated with immune infiltration levels. Conclusion: Collectively, our findings revealed that CD161 may serve as a potential biomarker for favorable prognosis and a promising immune therapeutic target in BC.